Ubiquitin signaling and the proteasome drive human DNA–protein crosslink repair - Essawy, Maram; Chesner, Lisa; Alshareef, Duha; Ji, Shaofei; Tretyakova, Natalia; Campbell, Colin (Nucleic acids research, 2023)
Abstract DNA–protein crosslinks (DPCs) are large cytotoxic DNA lesions that form following exposure to chemotherapeutic drugs and environmental chemicals. Nucleotide excision repair (NER) and homologous recombination (HR) promote survival following exposure to DPC-inducing agents. However, it is not known how cells recognize DPC lesions, or what mechanisms selectively target DPC lesions to these respective repair pathways. To address these questions, we examined DPC recognition and repair by transfecting a synthetic DPC lesion comprised of the human oxoguanine glycosylase (OGG1) protein crosslinked to double-stranded M13MP18 into human cells. In wild-type cells, this lesion is efficiently repaired, whereas cells deficient in NER can only repair this lesion if an un-damaged homologous donor is co-transfected. Transfected DPC is subject to rapid K63 polyubiquitination. In NER proficient cells, the DPC is subject to K48 polyubiquitination, and is removed via a proteasome-dependent mechanism. In NER-deficient cells, the DNA–conjugated protein is not subject to K48 polyubiquitination. Instead, the K63 tag remains attached, and is only lost when a homologous donor molecule is present. Taken together, these results support a model in which selective addition of polyubiquitin chains to DNA-crosslinked protein leads to selective recruitment of the proteasome and the cellular NER and recombinational DNA repair machinery. Graphical Abstract Graphical Abstract